Relative Quotas: Correct Answer to Uncertainty or Case of Regulatory Capture - Philippe Quirion (Fondazione Eni Enrico Mattei (FEEM), 2003)
There is a tendency among policy-makers and industry lobbyists toward "specific", "relative" or "output-based" quotas, i.e., freely distributed to firms proportionally to their output. With a stochastic analytical model, we demonstrate that relative quotas are dominated either by absolute quotas or by price instruments as regards expected social cost. Furthermore, price instruments entail a lower expected compliance cost than relative quotas. Why, then, do industry lobbyists favour quantity instruments over price instruments? A possible explanation is that if the industry anticipates that the State will underestimate output and overestimate the MAC curve slope, it has an interest in defending relative quotas. The problem is that in such a case, both the environmental damage and the social cost are higher with relative quotas than with absolute ones. The choice of relative quotas over price instruments or absolute quotas may thus be a case of regulatory capture, to use Stigler's vocabulary.
Keywords: D81; Q25; Q28; 330; Uncertainty; policy choice; environmental taxes; tradable permits; regulatory capture; Quotenregulierung; Umweltstandard; Ökosteuer; Emissionshandel; Theorie